Perancangan Sistem Presensi Magang Berbasis Web dengan QR Code pada DPMPTSP Kota Bandung - Herlyna Ismayanti; Rita Komalasari (Universitas Informatika dan Bisnis Indonesia, 2025)
The commonly used manual-based internship attendance system has various shortcomings, such as the risk of fraud, the difficulty of real-time monitoring, and slow data processing. This research aims to design and implement a web-based attendance system using QR Code at DPMPTSP Bandung City. The methodology used is the SDLC waterfall model, which involves the stages of needs analysis, design, implementation, testing, and maintenance. The system utilises QR Code technology to automatically record the attendance of interns, with additional features such as permit submission and downloadable real-time attendance reports. The results of black-box based testing show that the system runs well, fulfilling the functional and non-functional requirements that have been set. The implementation of this system is expected to improve the efficiency and accuracy of attendance recording.